Squamous Cell Carcinoma of The Gingiva: A Case Report and Literature Review - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (AVES PRESS LTD, 2015)
Squamous cell carcinoma (SCC) is the most frequent epithelial malignancy of the oral cavity which is characterized by variable clinical manifestations. It arises from dysplastic oral squamous epithelium. By considering the pathogenesis of SCC, the smooth and intact surface for this lesion is not usual. A 52-year-old female patient was refered to Marmara University, Faculty of Dentistry, Oral Diagnosis Clinic with a chief complaint of generalized swelling of the gingiva. There was neither significant medical and family history nor any history of medication. No bleeding was reported and submandibular lymphadenopathy (LAD) was noted. Buccal and a palatinal mucosal tissue of left maxillary first molar had a verrucous appearance. In addition to clinical examination, a smear biopsy and then incisional biopsy was performed and histopathological examination revealed the lesion had a malign characterization with a diagnosis of 'squamous epithelium carcinoma'. Consequently, the patient was referred to Ear, Nose and Throat (ENT) department where the lesion was treated by surgery.
Keywords: Squamous cell carcinoma; oral diagnosis; histopathological examination